Three-Component Coupling of Arenes, Ethylene, and Alkynes Catalyzed by a Cationic Bis(phosphine) Cobalt Complex: Intercepting Metallacyclopentenes for C–H Functionalization - Whitehurst, William G; Kim, Junho; Koenig, Stefan G; Chirik, Paul J (Journal of the American Chemical Society, 2022)
A cobalt-catalyzed intermolecular three-component coupling of arenes, ethylene, and alkynes was developed using the well-defined air-stable cationic bis(phosphine) cobalt(I) complex, [(dcype)Co(η6-C7H8)][BArF 4] (dcype = 1,2-bis(dicyclohexylphosphino)ethane; BArF 4 = B[(3,5-(CF3)2)C6H3]4), as the precatalyst. All three components were required for turnover and formation of ortho-homoallylated arene products. A range of directing groups including amide, ketone, and 2-pyridyl substituents on the arene promoted the reaction. The cobalt-catalyzed method exhibited broad functional group tolerance allowing for the late-stage functionalization of two drug molecules, fenofibrate and haloperidol. A series of control reactions, deuterium labeling studies, resting state analysis, as well as synthesis of substrate- and product-bound η6-arene complexes supported a pathway involving C(sp 2 )–H activation from a cobalt(III) metallacycle.